Classification and weighting of scientific journals according to indexed databases for use by the UCLA research office (Ágora de Heterodoxias, 2026)
The work presented in this document aims to design a system for the classification and weighting of scientific journals based on internationally recognized indexed databases, intended for use by the Research Office of the Universidad Centroccidental Lisandro Alvarado (UCLA). Developed as a special project, this study proposes an updated evaluation system to support the recognition of the institution’s researchers’ scholarly output, as reflected in their publications in scientific journals. To this end, a documentary literature review was conducted, involving the compilation and selection of information from existing evaluation systems applied in other countries and universities. This process enabled the analysis and comparison of different methodologies in order to refine a proposal that is straightforward to apply. The resulting system comprises six journal categories and a formula that allows journals to be weighted according to the number of databases in which they are indexed.
Keywords: scientific journals; scientific journal categorization system; SDGs; CDCHT-UCLA